2009
DOI: 10.1007/s10530-009-9550-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying DNA C-values to evaluate invasiveness of angiosperms: validity and limitation

Abstract: DNA C-values might be one of important indices in the evaluation of angiospermous invasiveness. To test this viewpoint, we compared DNA 1C-values and basic genome sizes in 3,676 angiosperms. The results suggest that: (1) the two nuclear values vary greatly among different groups, e.g., significantly higher in herbs than in trees, in monocots than in dicots, in perennials than in non-perennials; (2) the two nuclear values both have significant effects on plant invasiveness, especially in herbs, dicots, monocots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…Portulaca oleracea 's lifespan is very flexible, a quality that implies a high level of weediness and invasiveness (Rejmánek, ; Chen et al ., ). The lifespan was reported to be approximately three months in Canada (Miyanishi & Cavers, ) and northern India (Singh, ).…”
Section: Discussionmentioning
confidence: 97%
“…Portulaca oleracea 's lifespan is very flexible, a quality that implies a high level of weediness and invasiveness (Rejmánek, ; Chen et al ., ). The lifespan was reported to be approximately three months in Canada (Miyanishi & Cavers, ) and northern India (Singh, ).…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with our finding that whether a species has known polyploid variants was not a direct predictor of naturalization in the PBN model. Rather, the effect of polyploidy may operate indirectly by leading to a reduction in monoploid genome size as suggested by Chen, Guo, and Yin () and Leitch and Bennett (). Nor did species with polyploid cytotypes show significantly faster rates of naturalization in survival analyses, and the effect of polyploidy in regression models was weaker than that of genome size, particularly in uncultivated species.…”
Section: Discussionmentioning
confidence: 98%
“…There is very little experimental evidence available at this point that could effectively explain the prevalence of polyploidy amongst common and (particularly) invasive species. Recent comparative studies (Chen, Guo & Yin 2010) and experimental studies on Phlox drummondii , Solidago gigantea and Arabidopsis spp. (Vyas et al.…”
Section: Discussionmentioning
confidence: 99%
“…There is very little experimental evidence available at this point that could effectively explain the prevalence of polyploidy amongst common and (particularly) invasive species. Recent comparative studies (Chen, Guo & Yin 2010) and experimental studies on Phlox drummondii, Solidago gigantea and Arabidopsis spp. (Vyas et al 2007;Hull-Sanders et al 2009;Ni et al 2009) have shown that polyploids have a distinct advantage in photosynthetic efficiency, growth, reduced generation time, vigour and biomass over their diploid counterparts, but whether this or similar advantages are found more universally amongst polyploids is not known.…”
Section: Discussionmentioning
confidence: 99%